INOVASI PENGOLAHAN KOPI SUSU GULA AREN DI DESA GUDANG - Nadia; Anisa; Fandi Nugroho; Faisal Abdillah; Adelia Rohaeni; Herliana Firera; Nadia Karisma; Ahmad Zakiy; Dexa Egi Nassandi; Aang Praboyo; Indah Eka Sasfitri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Gudang Village is located in Simpang Rimba district, South Bangka Regency. In this village, there are many palm trees that grow behind resident's houses and also in the forests.Most people in there use palm sap to be processed into palm sugar. This palm sugar were produced by Gudang resident itself, individually in their own house. The purpose of this KKN program by Muhammadiyah University Bangka Belitung in the Gudang village is to increase the high value of processed palm sugar products through innovative products from palm sugar. Palm sugar milk coffee is an innovative product from palm sugar processing which can be an alternative for the community to increase their income. This dedication activities or community service activities carried out in Gudang Village, Simpang Rimba District, South Bangka Regency by KKN Muhammadiyah University Bangka Belitung students were carried out for 1 (one) month with socialization and practice methods, ranging from how to make products, make brands to product marketing using media social.